Analysis of Scale-up Parameters in 3D Silicon-Nanowire Lithium-Battery Anodes. Issue 5 (11th February 2020) - Schneier, Dan; Harpak, Nimrod; Menkin, Svetlana; Davidi, Guy; Goor, Meital; Mados, Edna; Ardel, Gilat; Patolsky, Fernando; Golodnitsky, Diana; Peled, Emanuel
Abstract : New, higher-capacity materials are required in order to address the growing need for batteries with greater energy density and longer cycle life for modern applications. We present here a study of silicon-nanowire (SiNW) anodes, synthesized via a novel, catalysts free and scalable chemical vapor deposition (CVD) on stainless-steel mesh. This is a continuation to our previous paper (Harpak et al., Nano Lett. (2019) http://pubs.acs.org/doi/10.1021/acs.nanolett.8b05127 ) that describes the progress we recently made. The study is focused on the adaptation of the SiNW anode in various large-scale configurations. Our research efforts have resulted in the successful scale-up of the silicon anode from Si/Li half-cells with high areal capacity of 14 mAh cm −2, to coin cells with commercial cathodes, industrial 1/3AAA cells and proof-of-concept multilayered pouch cells. Testing of our anodes in cylindrical cells demonstrated the applicability of these anodes in commercial lithium-ion batteries that can run for hundreds of cycles, withstanding fast charge and subzero temperatures. An all-solid Si/polymer electrolyte/NCA cell is also demonstrated as a proof of concept (POC). We assign the major degradation mechanism of the SiNW anodes to the growth of the SEI thickness and impedance during cycling. We found that the depth of lithiation/delithiation and the voltage profile of the cell significantly affect cell's stability.